Establishing a Nation - Kikilaga Nenfu - Angelo, Tony (Victoria University of Wellington Law Review, 1999)
There are many challenges in life. Some, such as climbing Mount Everest, circumnavigating the globe, landing on the Moon or exploring Mars, are reported as great human adventures. Few however could be more daunting than being empowered to establish one’s identity at a time when knowledge of any previous national identity has, with the passage of a century, largely being lost. That nevertheless is the task set for Tokelau, 1 a small Pacific nation – 6,500 people, of whom only 1,500 live in the cultural homeland and in three discrete villages separated by the high seas. Tokelau and New Zealand are not approaching this task by following the typical externally driven decolonisation process used by the United Kingdom for its colonies or New Zealand for the Cook Islands or Niue. This paper is concerned with tracing aspects of the semiautochthonous process so far followed by Tokelau.